Simulation framework of NBTI degradation in nano-scale p-MOSFETs from the perspective of hydrogen and non-hydrogen transport formalism / Hanim Hussin - Hussin, Hanim (2015)
The rapid downscaling of contemporary bulk CMOS devices has worsened the negative bias temperature instability (NBTI) of p-channel Metal-Oxide-Semiconductor-Field-Effect-Transistors (p-MOSFETs), which consequently degrades the performance and reduces the operational lifetime of the device. The main problem in assessing the level of degradation was due to the recovery components that underestimated the lifetime prediction and performance of the device. As the recovery component issues are solved by the implementation of ultra-fast technique measurement with the measurement done at ~100 ns delay, the reaction-diffusion (R-D) model was no longer reliable as the degradation does not obey the power law. The degradation accountable under the R-D model was only of that based on the generation of interface traps whereas the recoverable components had been glaringly ignored. Therefore, there is a need to accurately model the degradation components and understand their contribution to NBTI subsequently producing a reliable model to predict the lifetime of the devices. A simulation framework was developed to investigate the recovery characteristics of dynamic NBTI effects in conventional silicon dioxide (SiO2) dielectric p-MOSFETs based on the hydrogen diffusion and hole- trapping mechanisms. A sequence of train pulses were applied to the gate terminal of p-MOSFET in single and multiple runs, thus emulating repetitive cycles of stress and recovery. The characteristics of the recoverable component, R of dynamic NBTI are explained from the perspectives of the R–D model and hole-trapping mechanism. The understanding of the recovery and permanent components were further extended based on the simulation study on NBTI induced hole trapping in E’ center defects, which led to the de-passivation of interface trap precursors in high-k PMOSFET gate. The resulting degradation was characterized based on the time evolution of the interface and hole trap densities as well as the resulting threshold voltage shift. The simulation framework for probing the energy distribution of defect charges was developed by defining the effective energy distribution of defect charges to be distributed under, within and beyond the energy band gap. Under the stress condition, the hole traps were charged up and subsequently the recovery voltage was applied for the de-trapping process. The recovery voltage was applied in the positive direction in steps which permitted the Fermi level at the interface to move from below the valence band edge to above the conduction band edge thereby producing the requisite energy profile. The defect charges originated from different defects consisting of as grown hole traps (AHT), cyclic positive charges (CPC) and anti-neutralization positive charges (ANPC) as suggested by the experimental data. The CPC peak at Ef – Ev = 1 eV was apparent in the Fin Field Effect Transistor (FinFET) and planar hafnium, (Hf) based device, suggesting that it is Hf-related. In conclusion, this work has characterized the defect component's behaviour and its origin, producing simulation results which were in qualitative agreement with published measurements by other researchers. It is important to understand and simulate accurately the influence of NBTI in the initial design phase to guarantee the reliable operation of devices and circuits within a specific lifetime criterion.